School Performance and Video Games among Middle School Students in the Municipality of La Estrella- Antioquia (Colombia) - Restrepo Escobar, Sandra Milena (2019)
This paper considers the results obtained from a 2015 study on videogames and academic performance in Middle School students (12-14 years-olds) in four Colombian institutions in the municipality of La Estrella, Antioquia. Research methodology was empirical and analytical as well as descriptive and correlational. It included a sample of 335 students who completed a survey for problematic use of new technologies (NT) garnering the following results: males rather than females play videogames more frequently. There are also certain trends as to the types of videogames played by students that attend public vs private schools. Overall, students tend to play educational games that require mental agility less frequently. Although there was no significant relevance regarding academic performance and videogame usage, there were correlations found in time, space, age and performance. Recommendations are provided for educational institutions in using  videogames as part of their educational strategies as well as guidelines for parents on regulating use of NT at home.